Calculus - Duren, William L. (Lexington, Mass. : Xerox College Pub., 1972)
The main effort in writing these texts went into arranging the material so as to provide for flexibility and control of coverage in shorts courses.
Part One. Calculus of elementary functions -- Part Two. Multivariable calculus.
Includes index.
Keywords: CALCULUS